Perspectives of Childhood Cancer Symptom-Related Distress: Results of the State of the Science Survey - Skeens, Micah A. (J Pediatr Oncol Nurs, 2019)
Management of symptom-related distress is an important area of pediatric oncology nursing. Participants who attended the Children’s Oncology Group (COG) State of the Science Symposium on symptom distress completed an anonymous survey. The purpose was to explore participant perceptions of symptom distress experienced by children receiving cancer treatment on clinical trials, determine how symptom distress is currently assessed at COG institutions, and to identify what interventions are used to reduce symptom distress for these children. Among the 90 symposium attendees, 72% completed the survey, the majority (92%) of whom were nurses. The five most distressing symptoms in children with cancer enrolled on clinical trials identified by survey respondents were nausea/vomiting, fatigue, pain, anxiety, and sleep disturbances. Results from our survey also suggest that symptom distress may differ by disease type. For example, symptoms associated with leukemia/lymphoma included steroid side effects, procedural pain, and neuropathy. The majority of respondents (90%) also reported that symptoms go unrecognized by health care providers. The most commonly described unrecognized symptoms were behavioral (i.e., sadness, anxiety, fear, depression, and emotional needs; 45%) and fatigue (19%). Key focus areas reported by respondents included informal and inconsistent symptom assessment, the need for uniform measurement tools, and improved documentation of symptom-related distress. Management of symptom-related distress is an important aspect of pediatric oncology nursing. Further exploration of symptom distress experienced by children with specific types of cancers, and the development of standardized symptom assessment processes, will provide a foundation for developing future interventions aimed at alleviating symptom-related distress.